2013
DOI: 10.1503/cjs.035011
|View full text |Cite
|
Sign up to set email alerts
|

Acute general surgery in Canada: a survey of current handover practices

Abstract: Background: Today's acute care surgery (ACS) service model requires multiple handovers to incoming attending surgeons and residents. Our objectives were to investigate current handover practices in Canadian hospitals that have an ACS service and assess the quality of handover practices in place. Methods:We administered an electronic survey among ACS residents in 6 Canadian general surgery programs.Results: Resident handover of patient care occurs frequently and often not under ideal circumstances. Most residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Poor communication is a well-known hazard in clinical care, particularly at points of handover between providers. 22,23 We found problems in interdepartmental working were a key factor in many of the incidents in our study, particularly the transfer of fetal remains from maternity departments to the mortuary. Misidentification of patients is a common cause of wrong site surgery 24 and other patient safety incidents.…”
Section: Discussionmentioning
confidence: 69%
“…Poor communication is a well-known hazard in clinical care, particularly at points of handover between providers. 22,23 We found problems in interdepartmental working were a key factor in many of the incidents in our study, particularly the transfer of fetal remains from maternity departments to the mortuary. Misidentification of patients is a common cause of wrong site surgery 24 and other patient safety incidents.…”
Section: Discussionmentioning
confidence: 69%
“…18,19 Care may be compromised by frequent suboptimal transfers of care and a high turnover of busy nursing staff, surgeons and trainees. 20 Older adults cared for on these services commonly have evolving medical needs and multiple comorbidities. If undergoing urgent surgery, their health status often cannot feasibly be optimized preoperatively as would be done for patients undergoing elective operations.…”
Section: Discussionmentioning
confidence: 99%
“…In such an environment, disagreements over clinical management have the potential to significantly impact patient care – positively or negatively. A recent evaluation of acute care surgery handover practices indicated that problematic handovers could have a negative impact on patient outcomes, and the experience of learners [ 15 ]. In that study residents felt, that on average, inadequate handover contributed to at least a minor harm in 2.7 individual patients, and a major harm in 0.6 individual patients over the course of their training [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation of acute care surgery handover practices indicated that problematic handovers could have a negative impact on patient outcomes, and the experience of learners [ 15 ]. In that study residents felt, that on average, inadequate handover contributed to at least a minor harm in 2.7 individual patients, and a major harm in 0.6 individual patients over the course of their training [ 15 ]. With this evidence in mind, we feel that the clinical disagreements which occur when key patient care providers change over have the greatest potential to impact continuity of care, and ultimately affect patient outcomes.…”
Section: Discussionmentioning
confidence: 99%